2017
DOI: 10.1080/14789949.2017.1375541
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Violence Prevention Program: group and individual changes in aggression, anger, self-control, and empathy

Abstract: While youth violence reduction program is a necessity to prevent long-term criminal and violent offending, its effectiveness in youth violent offenders is not well researched. This study investigated the effectiveness of the Violence Prevention Program (VPP) in addressing the aggression, anger, self-control, and empathy of youth violent offenders. One hundred and seventy youths (mean age 15.8 years) who completed VPP from 2008 to 2014 completed self-report measures on study outcomes both before and after the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 69 publications
2
11
0
1
Order By: Relevance
“…Moreover, and consistent with the literature, results exhibited negative relations between gratitude and forgiveness with both types of bullying aggression [ 37 , 47 , 59 ]. In line with other scholars, we posit that forgiveness and gratitude hinder negative affect (for example, revenge and anger) [ 39 , 56 , 70 , 71 ], while encouraging positive affect (for example, compassion and empathy) [ 111 , 112 , 113 , 114 ]. The medium effect size indicates that this is of explanatory and practical use in the short run [ 110 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, and consistent with the literature, results exhibited negative relations between gratitude and forgiveness with both types of bullying aggression [ 37 , 47 , 59 ]. In line with other scholars, we posit that forgiveness and gratitude hinder negative affect (for example, revenge and anger) [ 39 , 56 , 70 , 71 ], while encouraging positive affect (for example, compassion and empathy) [ 111 , 112 , 113 , 114 ]. The medium effect size indicates that this is of explanatory and practical use in the short run [ 110 ].…”
Section: Discussionsupporting
confidence: 88%
“…Studies reported that high levels of self-control are related to less bullying perpetration [ 70 , 71 , 72 , 73 , 74 ]. A great deal of the literature indicates that self-control has a significant effect on proactive and reactive behaviors [ 18 , 75 , 76 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, forms of psychological support should be sought by people who have high levels of anger or desire to take justice into one’s own hands. For example, a study of 156 adolescent offenders found that a violence prevention program significantly reduced anger and aggression and produced improvements in self-control (Zhou et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Another issue regarding the psycho-rehabilitation programs is the implementation of social distancing measures and quarantine which may slow the recovery process of the inpatients. In addition, due to social distancing measures, group therapy sessions are not possible, and this can reduce the improvement on key therapeutic processes such as the development of insight, empathetic skills, and emotion regulation strategies (Zhou et al 2018). The problematic effects of the quarantine may also concern the implementation of occupational therapy pathways aimed to foster community reintegration (Perilli et al 2018).…”
Section: The Impact Of the Covid-19 Pandemic In Italymentioning
confidence: 99%